K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

22 tháng 8 2020

Bài làm:

Ta có: \(3\left(3-2x^2\right)+3x\left(2x-1\right)=9\)

\(\Leftrightarrow9-6x^2+6x^2-3x=9\)

\(\Leftrightarrow3x=0\)

\(\Rightarrow x=0\)

22 tháng 8 2020

\(3\left(2-2x^2\right)+3x\left(2x-1\right)=9\)

\(\Leftrightarrow3\left(2-2x^2+2x^2-x\right)=9\)

\(\Leftrightarrow2-x=3\)

\(\Leftrightarrow x=-1\)

25 tháng 8 2020

a) ( 3x + 2 )( x - 1 ) - ( x + 2 )( 3x + 1 ) = 7

<=> 3x2 - x - 2 - ( 3x2 + 7x + 2 ) = 7

<=> 3x2 - x - 2 - 3x2 - 7x - 2 = 7

<=> -8x - 4 = 7

<=> -8x = 11

<=> x = -11/8

b) ( 6x + 5 )( 2x + 3 ) - ( 4x + 3 )( 3x - 2 ) = 8

<=> 12x2 + 28x + 15 - ( 12x2 + x - 6 ) = 8

<=> 12x2 + 28x + 15 - 12x2 - x + 6 = 8

<=> 27x + 21 = 8

<=> 27x = -13

<=> x = -13/27 

c) 2x( x + 3 ) - ( x + 1 )( 2x + 1 ) - 5 = 9

<=> 2x2 + 6x - ( 2x2 + 3x + 1 ) - 5 = 9

<=> 2x2 + 6x - 2x2 - 3x - 1 - 5 = 9

<=> 3x - 6 = 9

<=> 3x = 15

<=> x = 5

d) ( 5x + 3 )( 4x - 7 ) - ( 10x + 9 )( 2x - 3 ) = 10

<=> 20x2 - 23x - 21 - ( 20x2 - 12x - 27 ) = 10

<=> 20x2 - 23x - 21 - 20x2 + 12x + 27 = 10

<=> -11x + 6 = 10

<=> -11x = 4

<=> x = -4/11

25 tháng 8 2020

a, \(\left(3x+2\right)\left(x-1\right)-\left(x+2\right)\left(3x+1\right)=7\Leftrightarrow-8x-4=7\Leftrightarrow x=-\frac{11}{8}\)

b, \(\left(6x+5\right)\left(2x+3\right)-\left(4x+3\right)\left(3x-2\right)=8\Leftrightarrow27x+21=8\Leftrightarrow x=-\frac{13}{27}\)

c, \(2x\left(x+3\right)-\left(x+1\right)\left(2x+1\right)-5=9\Leftrightarrow3x-6=9\Leftrightarrow x=5\)

d, \(\left(5x+3\right)\left(4x-7\right)-\left(10x+9\right)\left(2x-3\right)=10\Leftrightarrow-11x+6=10\Leftrightarrow x=-\frac{4}{11}\)

24 tháng 6 2017

a)\(2x\left(x+1\right)-3-2x=5\)

\(\Leftrightarrow2x^2+2x-3-2x=5\)

\(\Leftrightarrow2x^2=8\)

\(\Leftrightarrow x^2=4=\left(-2\right)^2=2^2\)

              \(\Rightarrow x=2;-2\)

b)\(2x\left(3x+1\right)+\left(4-2x\right)=7\)

\(\Leftrightarrow6x^2+2x+4-2x=7\)

\(\Leftrightarrow6x^2+4=7\)

\(\Leftrightarrow6x^2=3\)

\(\Leftrightarrow x^2=\frac{1}{2}=-\sqrt{\frac{1}{2}}=\sqrt{\frac{1}{2}}\)

c)\(\left(x-3\right)^3-\left(x-3\right)\left(x^2+3x+9\right)+6\left(x-1\right)^2=6\)

\(\Leftrightarrow x^3-9x^2+27x-27-x^3+27+6\left(x^2-2x+1\right)=6\)

\(\Leftrightarrow-3x^2+27x+6x^2-12x+6=6\)

\(\Leftrightarrow-3x^2+27x+6x^2-12x+6=6\)

\(\Leftrightarrow3x^2+15x=0\)

\(\Leftrightarrow3x\left(x+5\right)=0\)

         \(\Rightarrow\orbr{\begin{cases}3x=0\\x+5=0\end{cases}\Rightarrow}\orbr{\begin{cases}x=0\\x=-5\end{cases}}\)

11 tháng 11 2020

a)(x+2).(x+3)-(x-2).(x+5)=10

  ( x^2 +3x+2x+6)-(x^2 +5x-2x-10)=10

 x^2 +3x+2x+6-x^2 -5x+2x+10-10=0

 2x+6=0

2x=-6

x=-3

2 tháng 7 2018

(x+2)(x+3)-(x-2)(x+5)=0

=> x2+5x+6-x2-3x+10=0

=>2x+16=0 

 =>2x=-16

=>x=-8

2 tháng 11 2018

\(x^2-3x+2.\left(x-3\right)=0\)

\(x.\left(x-3\right)+2.\left(x-3\right)=0\)

\(\left(x-3\right).\left(x+2\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x=3\\x=-2\end{cases}}\)

\(x.\left(x-3\right)-3x+9=0\)

\(x.\left(x-3\right)-3.\left(x-3\right)=0\)

\(\left(x-3\right)^2=0=>x=3\)

2 tháng 11 2018

a,\(x^2-3x+2\left(x-3\right)=0.\)

\(\Leftrightarrow x^2-3x+2x-6=0\)

\(\Leftrightarrow x^2+x-6=0\)

\(\Leftrightarrow\left(x^2-2x\right)+\left(3x-6\right)=0\)

\(\Leftrightarrow x\left(x-2\right)+3\left(x-2\right)=0\)

\(\Leftrightarrow\left(x-2\right)\left(x+3\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x-2=0\\x+3=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=2\\x=-3\end{cases}}\)